Preservice Teachers’ Discriminatory Judgments - Riley, Tasha; Ungerleider, Charles (Alberta Journal of Educational Research, 2008)
Having pursued policies of human rights and multiculturalism, Canadians regard themselves as tolerant. Yet some critics say that when it comes to Aboriginals, Canadians seem xenophobic and discriminatory. This study is the first empirical test of whether Canadian preservice teachers’ judgments about the performance of Aboriginal students are discriminatory. Fifty preservice teachers were asked to assess the records of 24 students and recommend their placement in remedial, conventional, or advanced programs. Preservice teachers systematically devalued the performance of students whom they were led to believe were of Aboriginal ancestry in comparison with their non-Aboriginal counterparts with identical student records.